Synthesis and characterization of a novel series of meso (nitrophenyl) and meso (carboxyphenyl) substituted porphyrins - Schiavon,Marco A. (2000)
The anionic 5,10,15-tris(4-carboxyphenyl), 20-mono(2-nitrophenyl) porphyrin (1), 5,10(or 15)-bis(4-carboxyphenyl), 15(or 10),20-bis(2-nitrophenyl)porphyrin (2) and 5-mono(4-carboxyphenyl), 10,15,20-tris(2-nitrophenyl)porphyrin (3) were sinthesized directly by reaction of pyrrole with substituted benzaldehydes in nitrobenzene/propionic acid media. The benzaldehydes molar ratio was controlled to optimize the synthesis and purification of the desired porphyrins. This new series of porphyrins was characterised by TLC, mass spectrometry (FAB MS), ¹H NMR, UV/Vis, IR and electrochemistry. 5,10,15,20-Tetrakis(4-carboxyphenyl)porphyrin (4) and 5,10,15,20-Tetrakis(2-nitrophenyl)porphyrin (5) were also characterised for comparative purposes, completing the series The electrochemical reduction was investigated for the free base and corresponding iron(III) porphyrins on glassy carbon and mercury electrodes. The reduction potentials showed the expected dependence on the number of electron-withdrawing nitro groups present on the porphyrin ring providing additional evidences for the characterisation of the synthesised compounds.